Human brucellosis in Macedonia - 10 years of clinical experience in endemic region - Bosilkovski, Mile; Krteva, Ljiljana; Dimzova, Marija; Vidinic, Ivan; Sopova, Zaklina; Spasovska, Katerina (My University, 2010)
To present our 10-year clinical experience with brucellosis patients at the University Clinic for Infectious Diseases and Febrile Conditions in Skopje, Republic of Macedonia. A total of 550 patients with brucellosis treated between 1998 and 2007 were retrospectively assessed for their demographic, epidemiological, and clinical characteristics and outcomes. Of the 550 patients, 395 (72%) were male. The median age was 34.5 years (range, 1-82). Direct contact with infected animals was recorded in 333 (61%) patients and positive family history in 310 (56%). The most frequently seen symptoms were arthralgia (438, 80%), fever (419, 76%), and sweating (394, 72%). The most common signs were fever and hepatomegaly, which were verified in 357 (65%) and 273 (50%) patients, respectively. Focal brucellosis was found in 362 patients (66%) and osteoarticular in 299 (54%). Therapeutic failures were registered in 37 (6.7%) patients. Of the 453 (82%) patients who completed a follow-up period of at least 6 months, relapses occurred in 60 (13%). Due to non-specific clinical manifestation and laboratory parameters, brucellosis should be considered one of the differential diagnoses of any patient suffering from obscure involvement of various organs in a brucellosis-endemic region. High percentage of relapses and therapeutic failures in spite of the use of currently recommended therapeutic regimens indicates the seriousness of this zoonosis and the need to control it.